Dampak Kenaikan Subsidi BBM Terhadap Pendapatan Masyarakat Kampung Nelayan di Kelurahan Malabro: Dampak Kenaikan Subsidi BBM Terhadap Pendapatan Masyarakat Kampung Nelayan di Kelurahan Malabro - Putri Andini (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2023)
This study aims to determine how big the impact of this increase in fuel subsidies is on the income of fishermen in the Malabro Village. The method used is qualitative research methods and the data source used is primary data obtained through field studies, such as documentation and interviews. The data analysis technique used is the classical assumption test, simple linear regression test and hypothesis testing. see whether the data in the study are normally distributed or not, besides that this test is also conducted to see whether there are deviations in the study or not. This simple linear regression test is used to observe whether there is a relationship between variables X and Y. And hypothesis testing is used to find out the significance between X and Y variables. This research is intended to see how the increase in fuel subsidies impacts fishermen's income, from the results of this study it is found that fuel subsidies (X) have a significant effect on fishermen's income (Y) where the simple regression coefficient is 0.081 with a significant level of <0.001 , a coefficient of determination of 0.218 or 12.8% is obtained, meaning that the fuel subsidy variable is able to provide an explanation for the income variable of 12.8% while the remaining 78.2% is explained by other factors. Meanwhile, when viewed partially, the output tcount is greater than ttable, where tcount is 4.285 with a significance value of <0.001 and ttable is 1.997 so that tcount > ttable (4.285 > 1.997) this indicates a positive correlation of each fuel subsidy variable to the income variable and has a significant effect because of the sig output. is at <0.001 or less than 0.05.